Keberlanjutan dan Politik Luar Negeri Qatar Dalam Piala Dunia 2022 - Luerdi Luerdi (PT. Faaslib Serambi Media, 2026)
The FIFA World Cup 2022 was held in Qatar, despite facing doubts and criticism regarding the event. It was the first time for Qatar to host the mega-event and the first time in the Middle East. Qatar finally succeeded in hosting the event, and it was even framed as the most sustainable FIFA World Cup in the tournament’s history. The state also projected the world’s football tournament as part of foreign policy driven by its National Vision 2030. This study attempts to shed light on the sustainability aspects of Qatar’s World Cup and the state’s foreign policy in pursuing development, constituting several pillars: human, social, economic, and environmental development. This study employed the qualitative research method with a case study approach and descriptive analysis. Qatar definitely gained several benefits by hosting the event: having the opportunity to get knowledge and technology transfer, particularly in sustainable infrastructure development as well as management of global mega-events, introducing values and culture of Qatari society, strengthening economic diversification, and reinforcing the state’s role in promoting and advancing sustainable development in accordance with the National Vision 2030.